Distribution of CD4(pos) -, CD8(pos) - and regulatory T cells in the upper and lower gastrointestinal tract in healthy young subjects. - Martin Tauschmann (Public Library of Science (PLoS), 2013)
The gastrointestinal immune system is involved in the development of several autoimmune-mediated diseases, including inflammatory bowel disease, multiple sclerosis, and type 1 diabetes mellitus. Alterations in T-cell populations, especially regulatory T cells (Tregs), are often evident in patients suffering from these diseases. To be able to detect changes in T-cell populations in diseased tissue, it is crucial to investigate T-cell populations in healthy individuals, and to characterize their variation among different regions of the gastrointestinal (GI) tract. While limited data exist, quantitative data on biopsies systematically drawn from various regions of the GI tract are lacking, particularly in healthy young humans. In this report, we present the first systematic assessment of how T cells--including Tregs--are distributed in the gastrointestinal mucosa throughout the GI tract of healthy young humans by means of multi-parameter FACS analysis. Gastroduodenoscopy and colonoscopy were performed on 16 healthy volunteers aged between 18 and 32. Biopsies were drawn from seven GI regions, and were used to determine the frequencies of CD8(+)-, CD4(+)- and Tregs in the gastrointestinal mucosa by means of multi-parameter FACS analysis. Our data show that there is significant variation in the baseline T-cell landscape along the healthy human gastrointestinal tract, and that mucosal T-cell analyses from a single region should not be taken as representative of the entire gastrointestinal tract. We show that certain T-cell subsets in the gastrointestinal mucosa vary significantly among regions; most notably, that Tregs are enriched in the appendiceal orifice region and the ascending colon, and that CD8(pos) T cells are enriched in the gastric mucosa.